2020
DOI: 10.1002/admt.202000390
|View full text |Cite
|
Sign up to set email alerts
|

Large‐Area Uniform Polymer Transistor Arrays on Flexible Substrates: Towards High‐Throughput Sensor Fabrication

Abstract: Solution‐processable organic semiconductors can serve as the basis for new products including rollable displays, tattoo‐like smart bandages for real‐time health monitoring, and conformable electronics integrated into clothing or even implanted in the human body. For such exciting commercial applications to become a reality, good device performance and uniformity over large areas are necessary. The design of new materials has progressed at an astonishing pace, but accessing their intrinsic, efficient electrical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 46 publications
0
23
0
Order By: Relevance
“…The gap size extraction followed a method adapted from Kano et al [13] Having confirmed a-Lith as a suitable patterning technique for the manufacturing of planar asymmetric electrodes, we identified several conjugated polymers as candidate semiconductors since they combine solution processability and potentially high mobility. [14][15][16][17] Among those the C 16 IDT-BT polymer (Figure 2a) was chosen since it is known to exhibit superior hole transport properties and low contact resistance with Au electrodes in thin-film transistors (TFTs). [18][19][20][21][22] Moreover, recent work has demonstrated that p-doping of C 16 IDT-BT can result in improved organic TFTs with reduced contact resistance and record hole mobility.…”
Section: Resultsmentioning
confidence: 99%
“…The gap size extraction followed a method adapted from Kano et al [13] Having confirmed a-Lith as a suitable patterning technique for the manufacturing of planar asymmetric electrodes, we identified several conjugated polymers as candidate semiconductors since they combine solution processability and potentially high mobility. [14][15][16][17] Among those the C 16 IDT-BT polymer (Figure 2a) was chosen since it is known to exhibit superior hole transport properties and low contact resistance with Au electrodes in thin-film transistors (TFTs). [18][19][20][21][22] Moreover, recent work has demonstrated that p-doping of C 16 IDT-BT can result in improved organic TFTs with reduced contact resistance and record hole mobility.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the development of high-performance polymer FETs requires not only molecular design and mechanism study but also practical applications in related functional devices. Addition of molecular additives, such as dopants, crosslinkers, and photosensitizers, is an effective method to solve the complications in practical applications, including large-scale fabrication, 105,106 contact resistances, 107 long-term stability, 108,109 high-speed applications, 110 etc. For instance, contact doping by adding molecular dopants is one of the most used techniques to reduce contact resistance and improve transistor performance in both inorganic and organic FETs.…”
Section: Discussionmentioning
confidence: 99%
“…[ 1–5 ] Even with nearly amorphous microstructures, semiconducting polymers have achieved remarkable performance and film uniformity over large areas, a key requirement for practical applications. [ 6–10 ] One major problem faced in polymer‐based electronics is the inadvertent diffusion of atmospheric water through the soft constituent layers. Water is omnipresent and has been recognized as the main culprit in device degradation.…”
Section: Introductionmentioning
confidence: 99%
“…We focus on OFETs based on the donor‐acceptor copolymer indacenodithiophene‐ co ‐benzothiadiazole (IDT‐BT) ( Figure a), a material that has achieved charge carrier mobilities exceeding 1 cm 2 V −1 s −1 with very little device‐to‐device variations over large areas. [ 6,25–27 ] To uncover the physical processes occurring in the presence of water, we exposed IDT‐BT OFETs to a desiccant, similar to Nikolka et al., [ 11 ] and monitored the evolution of device parameters and the trap density of states (t‐DOS) during moisture removal. While the effect of water on the performance and stability of organic devices has been studied extensively, [ 11–13,23,24 ] here we show direct evidence for the formation of water‐induced trapping in the t‐DOS spectrum.…”
Section: Introductionmentioning
confidence: 99%